(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This research examines how a proposed increase in the intensity of physiotherapy forstroke patients in Saudi Arabia affects those patients’ long-term outcomes. Our goal was toexamine the effectiveness of CP in conjunction with a VR system designed to target the LE and todetermine whether or not this therapy was feasible and clinically effective for patients. We alsoaimed to evaluate how this system might influence motor skills, gait, balance, and trunk control inpost-stroke patients. Findings show that post-stroke functional improvement in LE and gait isgreater when a VR therapy is applied, with the help of enhanced feedback, than when the sameamount of CP treatment is used.